The Warsaw Ghetto in American art and culture - Baskind, Samantha (2018)
"An interdisciplinary study examining the diverse meanings of the Warsaw Ghetto in American culture. Looks at how the ghetto has been represented in fine art, book illustrations, film, television, radio, theater, fiction, poetry, and comics"...Provided by publisher